PERLINDUNGAN HUKUM BAGI KONSUMEN ATAS PRODUK OLI PALSU PADA E-COMMERCE (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The development of information and communication technology that is so fast with the existence of the internet, it has brought changes in the trading process which was originally carried out in the conventional way by meeting sellers and buyers (face to face) has changed with the existence of E-Commerce, namely buying and selling goods online using the internet as the main medium in business transactions. In E-Commerce, these business actors take advantage of the condition of consumers who can’t see, prove or even not understand if there is non-original or mixed vehicle oil. The purpose of this study is to determine the legal protection of consumers who buy counterfeit oil through E-Commerce and the responsibility of business actors for selling fake oil. This study uses a normative legal method with a statute approach. The results of this study, legal protection for consumers who buy counterfeit oil through E-Commerce is regulated in Article 4 in conjunction with Article 7 of Law Number 8 of 1999 concerning Consumer Protection. Next, the responsibility of business actors who sell counterfeit oil through E-Commerce is regulated in Article 1365 of the Civil Code in conjunction with Article 19 paragraph (2) of Law Number 8 of 1999 concerning Consumer ProtectionKeywords: Legal Protection, Responsibility, E-Commerce